2021
DOI: 10.3390/cells10071612
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Evidence for Sex Chromosomes and Karyotype Evolution in Anguimorphan Lizards

Abstract: Anguimorphan lizards are a morphologically variable group of squamate reptiles with a wide geographical distribution. In spite of their importance, they have been cytogenetically understudied. Here, we present the results of the cytogenetic examination of 23 species from five anguimorphan families (Anguidae, Helodermatidae, Shinisauridae, Varanidae and Xenosauridae). We applied both conventional (Giemsa staining and C-banding) and molecular cytogenetic methods (fluorescence in situ hybridization with probes fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 91 publications
(122 reference statements)
2
20
0
Order By: Relevance
“…These microchromosomes are tiny and dot-like; therefore, we cannot safely conclude whether the intense signal derives from ITRs or the extended arrays of terminal telomeres. A similar pattern has been identified in other reptilian species, such as the dragonsnake Xenodermus javanicus [ 66 ], monitors, and helodermatids [ 28 , 63 ]. One potential explanation is that microchromosomes often have higher recombination rates than autosomes in vertebrates, including birds and snakes [ 67 , 68 , 69 ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These microchromosomes are tiny and dot-like; therefore, we cannot safely conclude whether the intense signal derives from ITRs or the extended arrays of terminal telomeres. A similar pattern has been identified in other reptilian species, such as the dragonsnake Xenodermus javanicus [ 66 ], monitors, and helodermatids [ 28 , 63 ]. One potential explanation is that microchromosomes often have higher recombination rates than autosomes in vertebrates, including birds and snakes [ 67 , 68 , 69 ].…”
Section: Discussionsupporting
confidence: 77%
“…Considering that the chromosome morphology of this species is shared with other sand boas (except for E. colubrinus, as mentioned above), we suppose that ITRs in this species are likely an outcome of cryptic intrachromosomal rearrangements, such as inversions. Furthermore, the centromeric satellite content is very dynamic, and even closely related species might have a different composition of repeats [ 23 , 62 , 63 , 64 ]. FISH with telomeric probes did not detect ITRs in T. melanurus; however, the presence of the interstitial heterochromatin on the sixth chromosome pair might suggest a possible fusion point (e.g., tandem fusion), which might also explain the lower chromosome number (2n = 34) in this species compared with the typical snake karyotype (2n = 36).…”
Section: Discussionmentioning
confidence: 99%
“…In a later study, the occurrence of a ZW system of sex chromosomes was confirmed or suggested by cytogenetics in more species. More precisely, in A. lythrochila a putative W chromosome was identified on a minichromosome by C-banding, and both C-banding and CGH revealed a female specific signal in two other Anguidae species: Celestus warreni and Gerrhonotus liocephalus [246].…”
Section: Anguimorphamentioning
confidence: 99%
“…Knowledge of the karyotype is necessary in (cyto)genetics, or related fields, in order to study chromosomal rearrangements and abnormalities [5,6], the identification of sex chromosomes [7,8], and/or chromosome-specific genes [9]. Although chromosomal changes, (i.e., chromosomal losses, duplications, rearrangements), are strictly linked to a certain locus, without the knowledge of detailed karyotype, it is not possible to precisely identify chromosomal aberration, mutation or syndrome [10,11].…”
Section: Introductionmentioning
confidence: 99%